2009
DOI: 10.1111/j.1467-8624.2009.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ and Mothers’ Parenting Predicting and Responding to Adolescent Sexual Risk Behaviors

Abstract: Transactional models of problem behavior argue that less effective parenting and adolescent problem behaviors coevolve, exerting bidirectional influences. This article extends such models by analyzing growth trajectories of sexual risk behaviors and parenting processes among 3,206 adolescents (aged 13-18) and their residential parents. Within individuals, increases in regular family activities prospectively predicted declines in adolescents' risky sexual activities. In contrast, increases in risky sexual activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
124
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 60 publications
15
124
2
2
Order By: Relevance
“…Consistent with previous cross-sectional studies, we hypothesized that (a) teenage substance use would be prospectively associated with both DWI and RWI, and (b) positive parenting practices (parental monitoring knowledge and control) would be prospectively associated with decreased risk of teenage DWI and RWI. Given that the relationship between teenagers' and their parents' behavior can differ by gender (Coley et al, 2009;Luk et al, 2010), we explored possible differences in the associations in mother's and father's parenting practices and teenage RWI and DWI. However, we did not have pre-specifi ed hypotheses about the role of mothers versus fathers for decreasing the risk of DWI or RWI.…”
Section: Summary and Purpose Of The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous cross-sectional studies, we hypothesized that (a) teenage substance use would be prospectively associated with both DWI and RWI, and (b) positive parenting practices (parental monitoring knowledge and control) would be prospectively associated with decreased risk of teenage DWI and RWI. Given that the relationship between teenagers' and their parents' behavior can differ by gender (Coley et al, 2009;Luk et al, 2010), we explored possible differences in the associations in mother's and father's parenting practices and teenage RWI and DWI. However, we did not have pre-specifi ed hypotheses about the role of mothers versus fathers for decreasing the risk of DWI or RWI.…”
Section: Summary and Purpose Of The Current Studymentioning
confidence: 99%
“…Family activities play an important role in protecting adolescents from risky behaviors, but fathers and mothers may not be equally alert to or react the same in the face of problem behaviors (Coley et al, 2009). For example, father's and mother's communication with adolescents worked differently in protecting against smoking and substance use for sons and daughters (Luk et al, 2010).…”
Section: Factors Associated With Teenage Dwi and Rwimentioning
confidence: 99%
“…24 -26 Recently, studies have begun to look at the role of fathers in adolescents' sexual development, showing that, for instance, fathers' involvement may positively affect their children's sexual development. [27][28][29] To the authors' knowledge, 2 studies have investigated the association between the quality of the father-adolescent relationship and adolescents' sexual intercourse initiation. 27,28 These 2 studies found that adolescents who reported higher-quality relationships with their fathers at baseline (age = 15-19 years) were less likely to report sexual intercourse experience at follow-up (age = 16-19 years).…”
mentioning
confidence: 99%
“…Furthermore, our findings are in line with socioecological theory 17 and family systems theory, 59 which emphasize that various aspects of complex family environments, including the quality of parentadolescent relationships and parental monitoring, contribute to the timing of adolescents' sexual initiation. More empirical research is needed to further advance our understanding of how different family relationships (ie, father-son, father-daughter, motherdaughter, and mother-son dyads) 29,60 and other parenting practices (eg, levels of involvement, control, and sexual communication) interact with each other and influence adolescents' sexual development.…”
mentioning
confidence: 99%
See 1 more Smart Citation